SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL EVALUATION OF SUBSTITUTED 1,3,4-OXADIAZOLE DERIVATIVE: DERIVED FROM CIPROFLOXACIN - ANUJ SINGHAI; GUPTA , M.K. (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The purpose of this research is synthesized and evaluates different derivatives of oxadiazole. Methods: A novel series of substituted 1,3,4-oxadiazole derivative were synthesized by condensing different amine with 1-cyclopropyl-6-fluoro-7- (piperazin-1-yl)-3-(5-thioxo-4,5-dihydro-1,3,4-oxadiazol-2-yl)quinolin-4(1H)-one (III) in the presence of formaldehyde. The structure of these novel synthesized compounds was characterized on the bases of physicochemical and spectral analysis. The title compounds (IVa-h) were screened for antibacterial activity by disc diffusion method. Results: Substituted 1,3,4-oxadiazole derivative was synthesized, characterized, and evaluated for antibacterial activity. Compounds IVa, IVd, IVe, IVf, and IV h showed enhance activities then ciprofloxacin against all Gram-positive and Gram-negative organisms. Compound IVe showed the highest activity against Staphylococcus aureus and compound IV showed the highest activity against Escherichia coli. Conclusion: The present study demonstrates the synthesis and characterization of 1,3,4-oxadiazole derivatives derived from ciprofloxacin. These compounds were evaluated for antibacterial activity against different Gram-positive and Gram-negative organism. In some cases, antibacterial activity is found to be enhanced as compared to standard drug ciprofloxacin.